1982
DOI: 10.1029/gl009i004p00465
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of atmospheric velocity fluctuations at 8 km and 86 km

Abstract: Power spectra of wind variability (power spectral density vs. period) between roughly 3m and 8d are presented for the high‐latitude summer troposphere (8 km) and mesosphere (86 km). These results were obtained from an essentially continuous record of wind measurements using the Poker Flat MST radar in Alaska.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 22 publications
5
54
0
Order By: Relevance
“…The spectral amplitudes in the PBL increase more than one order of magnitude from the bottom to the top of the PBL, and the latter values are comparable to values in the mid-latitude upper troposphere and 1/100-1/30 those in the mid-latitude upper mesosphere (e.g., Balsley and Carter, 1982;Larsen et al, 1982;Nakamura et al, 1993), as shown in Fig. 4.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 51%
See 3 more Smart Citations
“…The spectral amplitudes in the PBL increase more than one order of magnitude from the bottom to the top of the PBL, and the latter values are comparable to values in the mid-latitude upper troposphere and 1/100-1/30 those in the mid-latitude upper mesosphere (e.g., Balsley and Carter, 1982;Larsen et al, 1982;Nakamura et al, 1993), as shown in Fig. 4.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 51%
“…A slope of -5/3 has been reported in observations in the extra-tropical lower and middle atmosphere in earlier studies however (e.g., Balsley and Carter, 1982;Larsen et al, 1982;Gage et al, 1986;Tsuda et al, 1994b). The slope for the meridional component in the dry season is gentler than -1 at frequencies less than 1 day-.…”
Section: Frequency Power Spectra Of Wind Velocity Fluctuationsmentioning
confidence: 67%
See 2 more Smart Citations
“…Here it should be remembered that there must be a systematic relation between the horizontal wavelength and the amplitude of vertical motion through the mesoscale region of IGW when we follow the energy spectrum observation by Balsley and Carter (1982). Therefore, we cannot select both wave parameters independently.…”
Section: Introductionmentioning
confidence: 99%